eBryoSoil: a citizen science application to monitor changes in soil ecosystems - André F. Mira; Joaquín Hortal; Ana Paula Portela; Belén Albertos; Belén Estébanez; Cristina Branquinho; Cristiana Vieira; Helena Hespanhol; Isabel Draper; Joana Marques; Juliana Monteiro; María Leo; et al. (Scientific Reports)
Abstract Biological soil covers (BSCs) play a pivotal role in ecosystem functioning by enhancing soil stability, mediating nutrient cycling, and influencing soil hydrology. Recognized as ecosystem engineers, they can physically modify, maintain, or create habitats, facilitating plant community development. Through these intricate interactions, BSCs contribute significantly to ecological processes, highlighting their importance in the overall health and functionality of the ecosystems of the Iberian Peninsula. Here we present the results obtained from the contributions of the citizen scientists uploaded from November 2019 to January 2021 with eBryoSoil, an app that allows citizens to participate in mapping the BSC communities across the Iberian Peninsula. Here, we emphasize the importance of habitats and consequently, their interaction with climatic variables for the persistence of BSCs (lichens and bryophytes). Conservation efforts targeted at preserving diverse habitats are essential to ensure the continued presence of lichen and bryophyte communities. Despite challenges posed by the SARS-CoV-2 outbreak, this citizen science project demonstrated success in utilizing a specifically tailored app to gather valuable information on BSC communities, providing insights into their vulnerability to climate change. This program serves as an illustrative example of how citizen science can effectively identify and study vulnerable habitats, offering a blueprint for future studies focused on understudied organisms.